2017
DOI: 10.1038/s41598-017-07894-2
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean Section is associated with reduced perinatal cytokine response, increased risk of bacterial colonization in the airway, and infantile wheezing

Abstract: The relationship between cesarean section (CS) and allergic disorders such as asthma and wheezing has been inconsistent, and the mechanisms for their connection remained largely unknown. We aimed to investigate whether CS is associated with infantile wheeze and to explore the connection between CS and several risk factors known to correlate with allergy development. Mononuclear cells were isolated from cord blood and assessed for cytokine responses by ELISA. Bacteria from nasopharyngeal specimens were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 33 publications
0
19
0
7
Order By: Relevance
“…The Prediction of Allergy in Taiwanese Children (PATCH) study, a prospective birth cohort of 579 children, reported that CS was associated with an increased incidence of ‘wheeze’ and reduced lung function at 12 months of age (Liao et al . ). Furthermore, these infants had impaired neonatal production of pro‐inflammatory cytokines in isolated mononuclear cells linking mode of delivery with development of the neonatal immune system (Liao et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The Prediction of Allergy in Taiwanese Children (PATCH) study, a prospective birth cohort of 579 children, reported that CS was associated with an increased incidence of ‘wheeze’ and reduced lung function at 12 months of age (Liao et al . ). Furthermore, these infants had impaired neonatal production of pro‐inflammatory cytokines in isolated mononuclear cells linking mode of delivery with development of the neonatal immune system (Liao et al .…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, these infants had impaired neonatal production of pro‐inflammatory cytokines in isolated mononuclear cells linking mode of delivery with development of the neonatal immune system (Liao et al . ; Chu et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…According to an increasing number of epidemiologic studies, children delivered by cesarean section more commonly developed respiratory and neurological disorders (e.g., autism spectrum disorders [11], schizophrenia [12]) and immune-related diseases, such as asthma [13,14], skin atopy [15], juvenile arthritis, coeliac disease [16], type 1 diabetes (T1D) [17] or obesity [1,[18][19][20][21][22][23]. It is worth noting differences between the occurrence of the above-mentioned conditions in cases when the surgical procedure was performed after delivery had started.…”
Section: Introductionmentioning
confidence: 99%
“…Родовой стресс является пусковым механизмом активации различных цитокинов, способствует активации иммунной системы новорожденного, что доказано как для вагинальных родов, так и родов путем кесарева сечения, проводимого в периоде начавшейся родовой деятельности [8]. Изменение естественного родового процесса может привести к отрицательному воздействию на активацию системы иммунитета младенца [9]. Перед родами и во время родов в условиях гипоксии и ацидоза происходит образование большого числа биоактивных веществ в организме матери и плода, способствующих физиологической перестройке всех органов и систем к адаптационному периоду [10].…”
unclassified
“…Механизмы, в полной мере объясняющие влияние способа родоразрешения на развитие бронхиальной астмы у детей, ясны не до конца. Предполагают, что оперативное родоразрешение приводит к изменению врожденных иммунных реакций (снижение продукции ФНО-α и ИЛ-6 для стимуляции TLR 1-2) в раннем возрасте и к обильной бактериальной колонизации дыхательных путей у детей в старшем возрасте с нарушением равновесия Th1/Th2 лимфоцитарного ответа [15]. TLR-рецепторы занимают центральное место среди наследственно-закодированных рецепторов PRRs (паттерн-распознающих рецепторов), которые регулируют адаптивный иммунный ответ и влияют на дифференцировку Th1/Th2 так же, как и биомаркер аллергической сенсибилизации (IgE) [16].…”
unclassified